Iron stores and coagulation parameters in patients with hypoxemic polycythemia secondary to chronic obstructive pulmonary disease: the effect of phlebotomies - Martinez, José Antônio Baddini; Guerra, Celso Carlos de Campos; Nery, Luiz Eduardo; Jardim, José Roberto de Brito (São Paulo Medical Journal, 1997)
This study was designed to determine the effects of phlebotomy on iron body contents and coagulation tests of COPD patients with polycythemia secondary to hypoxemia. Seventeen patients with COPD and hematocrits higher than 54 percent (mean Hct: 57 ± 0.49 percent ), who had not received anti-inflammatory or antiplatelet aggregation agents recently. Their mean forced expiratory volume at 1 second (FEV1) was 0.92 ± 0.11 L. Intervention: Blood work was collected to evaluate the following: serum iron and ferritin levels, total iron binding capacity, transferrin saturation index, fibrinogen plasma levels, activated partial thromboplastin time, platelet count, platelet aggregation measurements, and thromboelastography coagulation parameters. The blood samples were obtained before and about 7 days after the hematocrit correction by 300-400 ml phlebotomies done every other day. The mean number of phlebotomies done for each patient was 4.4. Postphlebotomy iron serum levels decreased from 90.1 ± 14.8 to 59.7 ± 9.9 mg/dl and the ferritin serum levels from 133.8 ± 37.9 to 70.8 ± 32.7 ng/ml (p< 0.05). Regarding the coagulation studies, there were significant increases in the platelet count, from 227,300 ± 13,900 to 312,500 ± 30,200 per mm³, and in the maximum clot amplitude (a) obtained by thromboelastography ( from 53.6 ± 1.4 percent to 60.4 ± 1.1 percent). The coagulation time (k) of the thromboelastography also decreased significantly, from 7.5 ± 0.7mm prephlebotomy to 4.5 ± 0.3mm postphlebotomy. Although the coagulation changes were small amount, the observed significant decrease in iron contents may have important clinical implications.